2018
DOI: 10.1051/0004-6361/201833528
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of double peaked Lyα emission at z = 6.593

Abstract: Distant luminous Lyman-α emitters (LAEs) are excellent targets for spectroscopic observations of galaxies in the epoch of reionisation (EoR). We present deep high-resolution (R = 5000) VLT/X-shooter observations, along with an extensive collection of photometric data of COLA1, a proposed double peaked LAE at z = 6.6. We rule out the possibility that COLA1’s emission line is an [OII] doublet at z = 1.475 on the basis of i) the asymmetric red line-profile and flux ratio of the peaks (blue/red=0.31 ± 0.03) and ii… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 118 publications
3
91
0
Order By: Relevance
“…In both cases, the minimum UV luminosity of the contributing sources is M min UV < −20.0 (2σ). In practice however, a model where only galaxies brighter than M UV = −20.0 is implausible because it would require an overhelmingly high luminosity-averaged escape fraction of ≈ 1, contradicting existing z ∼ 6 measurements (Matthee et al 2018) and marking a stark departure from measurements at lower-redshift (e.g. Vanzella et al 2016;Izotov et al 2016Izotov et al , 2018Tanvir et al 2019;Fletcher et al 2019).…”
Section: Relative Contribution Of Sub-luminous Sourcesmentioning
confidence: 94%
See 1 more Smart Citation
“…In both cases, the minimum UV luminosity of the contributing sources is M min UV < −20.0 (2σ). In practice however, a model where only galaxies brighter than M UV = −20.0 is implausible because it would require an overhelmingly high luminosity-averaged escape fraction of ≈ 1, contradicting existing z ∼ 6 measurements (Matthee et al 2018) and marking a stark departure from measurements at lower-redshift (e.g. Vanzella et al 2016;Izotov et al 2016Izotov et al , 2018Tanvir et al 2019;Fletcher et al 2019).…”
Section: Relative Contribution Of Sub-luminous Sourcesmentioning
confidence: 94%
“…Direct measurements of the ionising parameters of galaxies have proven challenging and offer a fractured picture. Spectroscopy of the afterglow of gamma ray bursts indicate extremely low escape fractions 2 % for their hosts (Tanvir et al 2019), whereas the peak separation of Lyman-α in a bright LAE (COLA1) results in an indirect measurement of f esc ∼ 15 − 30 % (Matthee et al 2018). Individual galaxies at high redshift have been found to have hard radiation spectra (e.g.…”
mentioning
confidence: 99%
“…The luminous Lyα emitter, COLA1 at z = 6.6 (f esc ∼ 30%, M UV = −21.5, Σ SFR = 100 M /yr/kpc 2 ) is a poster-child oligarch (Hu et al 2016;Matthee et al 2018). It displays double-peaked Lyα with a low-peak separation reminiscent of local LyC leakers (Verhamme et al 2017).…”
Section: Observing the Oligarchs In Action: Promisingmentioning
confidence: 99%
“…A few of the most-luminous LAES at z 6 have already received observational attention (e.g. Ouchi et al 2009;Lidman et al 2012;Hu et al 2016;Matthee et al 2018), with one object being suggested to either host metal-free stars (Sobral et al 2015) or a direct-collapse black hole (Pallottini et al 2015). At z ∼ 2−3 Sobral et al (2018b) presented recently spectroscopic results on 20 bright LAEs (log L Lyα [erg s −1 ] > 42.7).…”
Section: -1mentioning
confidence: 99%